2021
DOI: 10.2147/cmar.s305939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Regorafenib in Delaying Definitive Deterioration in Health-Related Quality of Life in Patients with Advanced Cancer of Three Different Tumor Types

Abstract: The efficacy and safety of regorafenib have been demonstrated in phase 3 trials for multiple tumor types, including metastatic colorectal cancer (mCRC) (CORRECT [NCT01103323]; CONCUR [NCT01584830]), advanced gastrointestinal stromal tumor (GIST) (GRID [NCT01271712]), and hepatocellular carcinoma (HCC) (RESORCE [NCT01774344]). The objective of this post hoc exploratory analysis was to explore the impact of regorafenib on delaying health-related quality of life (HRQOL) deterioration across these tumor types. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…This hypothesis is further supported by other phase 3 trials that assessed time to deterioration and also showed longer TTdD in treatment arms with significantly or numerically favourable efficacy. These results were consistent across indications including renal cell carcinoma (in a trial of LEN in combination with PEMBRO or everolimus compared with sunitinib) [ 7 , 19 ], hepatocellular carcinoma (in a non-inferiority trial comparing LEN vs sorafenib) [ 20 , 21 ], and a pooled analysis of four trials comparing regorafenib versus placebo across three tumour types [ 22 ].…”
Section: Discussionmentioning
confidence: 62%
“…This hypothesis is further supported by other phase 3 trials that assessed time to deterioration and also showed longer TTdD in treatment arms with significantly or numerically favourable efficacy. These results were consistent across indications including renal cell carcinoma (in a trial of LEN in combination with PEMBRO or everolimus compared with sunitinib) [ 7 , 19 ], hepatocellular carcinoma (in a non-inferiority trial comparing LEN vs sorafenib) [ 20 , 21 ], and a pooled analysis of four trials comparing regorafenib versus placebo across three tumour types [ 22 ].…”
Section: Discussionmentioning
confidence: 62%
“…Regorafenib is a third-line treatment for GIST patients but is also registered as a treatment for hepatocellular carcinoma (HCC) and metastatic colorectal cancer (mCRC). Hofheinz et al pooled HRQoL data of patients treated with regorafenib in four trials, including GIST, HCC, and mCRC patients [ 154 ]. Across all tumor types, regorafenib significantly delayed the patient’s first clinical important deterioration in HRQoL score, with the median time to HRQoL deterioration ranging from 16–24 weeks for regorafenib compared to 8–12 weeks for placebo.…”
Section: Discussionmentioning
confidence: 99%
“…And for patients who progress from sorafenib, regorafenib may offer longer survival and better tolerability and safety than cabozantinib. Furthermore, a recent analysis showed patients' quality of life is significantly better maintained with regorafenib than with placebo [ 31 ]. Further investigations are needed to determine the optimal treatment option for patients progressing from immunotherapy or lenvatinib frontline treatment.…”
Section: Discussionmentioning
confidence: 99%